Integrating molecular genetics and evolutionary psychology: Sexual jealousy and the androgen receptor (AR) gene. (1st January 2018) - Lewis, David M.G.; Al-Shawaf, Laith; Janiak, Mareike C.; Akunebu, Sarah P.
Abstract: Integrating evolutionary psychological and molecular genetic research may increase our knowledge of the psychological correlates of specific genes, as well as enhance evolutionary psychology's ability to explain individual differences. We tested the hypothesis that men's sexual jealousy mechanisms functionally calibrate their psychological output according to genetic variation at the androgen receptor locus. Mated men ( N = 103) provided buccal cell samples for genotype fragment analysis and completed inventories assessing their sexually jealous cognitions and emotions. Results indicated that men with longer sequences of CAG codon repeats at the androgen receptor locus were more likely to perceive ambiguous social and environmental cues as indicative of their mates' infidelity, and experienced greater emotional upset in response to these cues. These results contribute to a growing body of research linking polymorphism at the AR locus to individual differences in psychology, and, to our knowledge, provide the first evidence pointing toward the heritability of sexual jealousy. Our discussion centers on whether the heritability of psychological differences implies direct genetic influences on the neurobiological substrate, or reflects functionally calibrated output from sex-typical and species-typical mechanisms. We conclude by describing how future research can more clearly differentiate between these alternative genetic models. Highlights: Evolutionary psychology and molecular genetics can usefully inform one another. 103 mated men provided genetic samples and completed sexual jealousy inventories. Longer alleles at the AR locus predicted more frequent sexually jealous cognitions. Men with longer alleles also experienced more intense emotional jealousy. These findings provide the first evidence of the heritability of sexual jealousy.